Rahmah Based Education - Mawaddah Nasution (Proceeding International Seminar of Islamic Studies, 2019)
Education is the most basic thing that must be possessed by every human being for his survival. Education does not escape from the participation of teachers and parents in carrying it out. In transferring education that will be delivered to children must be based on mercy or affection in accordance with what is in the Qur'an, because children who are given education on the basis of mercy or affection will grow into children who have good hearts, warm and can love the people around him. In addition, children who are raised and get education on the basis of mercy will grow into brave children, able to compete in the future. The Rahmah approach taught by God in the Qur'an can also be a counseling therapy for troubled children.